The Konsekuensi dari Ekosistem Digital terhadap Regulasi Persaingan Bisnis di Indonesia dan Peran Komisi Pengawas Persaingan Usaha (KPPU) dalam Era Ekonomi Digital: Ekosistem Digital terhadap Regulasi Persaingan Bisnis di Indonesia - NI MADE, TRISNA DEWI (VYAVAHARA DUTA, 2024)
The era of the digital economy as it is today has demanded business people to carry out their business activities online. As a result, buyers will also make purchases online. It has implications for business competition. In this case, Law (UU) No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair business Competition has not accommodated the impact of the digital economy. So with that, this research has two objectives. The objectives are; First, to know the effect of the digital ecosystem on business competition law in Indonesia. Second, to see the role of the Business Competition Supervisory Commission (KPPU) in the digital economy era in the event of unfair business competition. This research uses the type of juridical-normative research. The impact of the digital economy on business competition in Indonesia has resulted in a lot of abuse of the digital platform market. In this case, digital platforms are increasing with vertical business development. This business development increases the ability of digital platforms to collect more data, increase their competitiveness and become online shop owners and application users, so that the dominant position of digital platforms can be abused, for example, discriminating against competitors in retail, exclusivity agreements with consumers, and selling policies. With losses may result in competitors becoming uncompetitive in the market and leaving the market. Responding to these challenges, it is necessary to have a regulation that regulates in a more specific scope. This is because several countries in Europe have revised their business competition law regulations to protect business actors. In addition, as a form of responding to the challenges of the times that have changed the direction of the economy and online business. Of course, the government and business actors must work together to achieve good goals for the parties who will have an impact.